Elevated cortisol levels in Norwegian toddlers in childcare. Issue 12 (2nd December 2018) - Drugli, May Britt; Solheim, Elisabet; Lydersen, Stian; Moe, Vibeke; Smith, Lars; Berg-Nielsen, Turid Suzanne
ABSTRACT: Meta-analytic evidence suggests that children have higher cortisol levels in childcare than at home. In the present study change of morning to mid-afternoon levels of cortisol was explored at home and in childcare in a Norwegian sample of toddlers. Further, analyses of associations between change of cortisol levels in childcare and child-, family-, and childcare factors were conducted. One hundred and twelve children attending 85 childcare centres were included in the present study. Saliva samples and observations in childcare were conducted 5–6 months after the children entered childcare. Linear mixed-model analyses revealed a statistical significant difference in change of cortisol levels during the day in childcare as compared at home. An increase in cortisol levels during the day was found among Norwegian toddlers in childcare, in particular for children with long hours in childcare, but not at home. Implications for practice are discussed.